The Australian judiciary - Lee, H. P., 1947-; Campbell, Enid Mona, 1932- (Cambridge : Cambridge University Press, 2013)
'This new edition follows the scheme of the first edition of the book. As was stated in the first edition, the principal aim of this book is to contribute to a better understanding of the Australian judiciary. Australians are entitled to engage in critical discussions about the judicial branch of government, as is befitting a healthy democracy. However, when they do so, it should be from an informed standpoint. Sir Gerard Brennan, Chief Justice of the High Court of Australia 1995-1998, said:'--
The courts and judges -- The judiciary as a branch of government -- Appointment and conditions of service -- Removal, suspension and discipline of judges -- Judicial conduct -- Extra-judicial activates of judges -- Protecting judicial institutions -- The accountability of judges -- A public trust.
Rev. ed. of: The Australian judiciary / Enid Campbell, H.P. Lee. 2001.
Includes bibliographical references and index.
Keywords: Justice, Administration of -- Australia; Courts -- Australia; Judges -- Australia